E-XY: an entropy based XY routing algorithm. (2019) - Punhani, Akash; Kumar, Pardeep
In recent years, Network on Chip (NoC) is used to handle the communication issues between cores or processing elements. The major drawback of existing XY routing algorithm for mesh topology is its inability to handle a high traffic load. In this paper, an E-XY (Entropy based XY) routing algorithm is proposed to generate information about the adjacent router based on previously communicated packets. Tests have been carried out on a mesh topology of 8x8 simulated using Omnet++ 4.4.1 using HNOCS version. Different types of traffic have been considered for result computation including uniform, bit complement, neighbour and tornado. The proposed algorithm is compared with other routing algorithms including XY, IX/Y and Odd Even. Results demonstrate that the proposed algorithm is comparable to XY routing algorithm up to the load factor of 0.8 and performs well than the XY, IX/Y and Odd Even routing algorithms with the increase in load.